Dynamic Cytoophidia during Late-Stage Drosophila Oogenesis - Zhang, S; Liu, J (MDPI, 2024)
CTP synthase (CTPS) catalyzes the final step of de novo synthesis of CTP. CTPS was first discovered to form filamentous structures termed cytoophidia in Drosophila ovarian cells. Subsequent studies have shown that cytoophidia are widely present in cells of three life domains. In the Drosophila ovary model, our previous studies mainly focused on the early and middle stages, with less involvement in the later stages. In this work, we focus on the later stages of female germline cells in Drosophila. We use live-cell imaging to capture the continuous dynamics of cytoophidia in Stages 10–12. We notice the heterogeneity of cytoophidia in the two types of germline cells (nurse cells and oocytes), manifested in significant differences in morphology, distribution, and dynamics. Surprisingly, we also find that neighboring nurse cells in the same egg chamber exhibit multiple dynamic patterns of cytoophidia over time. Although the described dynamics may be influenced by the in vitro incubation conditions, our observation provides an initial understanding of the dynamics of cytoophidia during late-stage Drosophila oogenesis.